Role of city collaboration networks in the acceleration and attenuation of integrated water management - Lena Berger (IWA Publishing, 2021)
Inter-city collaboration has gained prominence as a strategy to share practical experience and accelerate the spread of novel sustainability practices. This study explores the potential of collaboration as a means to foster the uptake of integrated water management (IWM). IWM is an innovative approach to water management regarded as key to achieving urban water sustainability. The uptake of IWM has generally been slow due to organizational and institutional challenges. To explore the potential of collaboration to accelerate uptake, we analyze collaboration among 45 cities in Arizona, USA, relative to their IWM engagement and organizational capacity. We find that collaboration patterns reflect cities’ interest in learning about innovative practices. However, there is a tendency to primarily collaborate with others who are in close geographic proximity. IWM practices and organizational capacities are secondary drivers of collaboration. Overall, our findings show opportunities while also urging realistic expectations. Highlights Cities that are more knowledgeable and diverse in their IWM practices tend to collaborate more.; Geographic proximity is the central criterion for the selection of collaboration partners; IWM practices and organizational capacities are secondary criteria.; To accelerate the adoption of IWM, cities may find it helpful to build relationships with farther afield partners while also using the power of local relationships.;